A break of day - Forrest, Bella (Forrest, Bella. Shade of vampire, 2014)
The greatly anticipated conclusion to Derek and Sofia's journey! Everything Sofia believed to be true has crumbled before her very eyes... In this explosive finale, secrets will be revealed, loyalties tested and trust broken.